Cutting forces in turning of gray cast iron using silicon nitride based cutting tool - Souza, J. V. C.; Nono, M. C. A.; Ribeiro, M. V. [UNESP]; Machado, J. P. B.; Silva, O. M. M. (Elsevier B.V., 2009)
This paper presents the results of an experimental investigation about the effect of cutting forces on gray cast iron turning using silicon nitride (Si(3)N(4)) based ceramic tool. Turning experiments were carried out at five different cutting speeds and feed rates while depth of cut was kept constant. Tool performance was evaluated with respect to tool wear, temperature, surface finish produced and cutting forces generated during turning. The Si(3)N(4) based ceramic cutting tool showed high performance when increasing cutting speed. These results can be associated with good high-temperature strength of the cutting tool and the presence of graphite flakes in gray cast iron, that lower the friction coefficient between the cutting tool/workpiece. (C) 2008 Elsevier Ltd. All rights reserved.